(3GdLhGH GdbGWY ddJehjg YeG jQO Hg Ydi GdMceI hGdJfRjgs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdMcje GdPi CWdYfG Ydi eYQaI CSQGQ JfRjdg hHYO , aMb Ydi ef JSQHd HSQHGd GdfXGQ hLQi ai LdSGJ GdJMbjb Cf jchf geg GdPH YeG jQO Ydi GdOjf ef THg Cgd GdRjZ s
(3BNQgG (B:s
(3hdfbJUQ Ydi gPG GdbOQ ef GdEdRGeGJ aajg ebfY hcaGjI hef CQGOgG HGSJbUGA ef cJGHfG GdedbH HGdTGed Je GdLhGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B143s
Keywords: (3GdJhMjO hGdedd hGdfMds